1999
DOI: 10.1046/j.1365-2273.1999.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised clinical trial of antiseptic nasal carrier cream and silver nitrate cautery in the treatment of recurrent anterior epistaxis

Abstract: Sixty-four consecutive patients with a history of recurrent epistaxis were randomly assigned in the outpatient clinic to receive treatment with either Naseptin antiseptic nasal carrier cream alone (Group A) or a combination of Naseptin cream and silver nitrate cautery (Group B). Results were available on 50 patients, 22 in Group A and 28 in Group B. Twenty patients (91%) in Group A and 25 patients (89%) in Group B demonstrated improvement in their symptoms. There was no statistically significant difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 11 publications
3
45
0
Order By: Relevance
“…The clinician who decides to cauterize faces off another decision: a single stage bilateral cauterization or unilateral cauterization necessitating a second stage. Up to date, bilateral simultaneous septal cauterization was avoided due to fear of septal perforation [3,7,11]. However, this avoidance is not supported by clinical studies but declared according to the personal experiences of the clinicians.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The clinician who decides to cauterize faces off another decision: a single stage bilateral cauterization or unilateral cauterization necessitating a second stage. Up to date, bilateral simultaneous septal cauterization was avoided due to fear of septal perforation [3,7,11]. However, this avoidance is not supported by clinical studies but declared according to the personal experiences of the clinicians.…”
Section: Discussionmentioning
confidence: 93%
“…Usually, unilateral septal cauterization is preferred and bilateral simultaneous cauterization is avoided because of fear of septal perforation [3,7]. There are only a few clinical studies concerning simultaneous bilateral cauterization of the nasal septum in children [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, and with an examination demonstrating prominent vessels on both sides of the anterior septum, the clinician is faced with a consideration of treating both areas of the septum in one visit or having the patient return for a second visit to avoid cauterization of both sides of the septum at one time. In a recent publication assessing the efficacy of silver nitrate cauterization compared to the use of nasal ointment in the control of epistaxis the complication of septal perforation associated with silver nitrate was described as ''well known'' [2]. Although this anecdotal evidence of risk of septal perforation involved in cauterization of the septum exists, the authors could find no published data specifically addressing the topic of bilateral epistaxis and the efficacy and risk involved in bilateral septal cauterization in children.…”
Section: Discussionmentioning
confidence: 95%
“…4 An earlier clinical trial also found that chemical nasal cautery added no bene t over antiseptic/antibiotic cream alone. 5 Yes, it seems we all love Naseptin, but how many of us speci cally check for peanut allergy prior to prescribing? S.A. Hannan, M.R.C.S., D.L.O.R.C.S.…”
mentioning
confidence: 99%